Still slow, but even steadier: an update on the evolution of turtle cranial disparity interpolating shapes along branches. Issue 11 (29th November 2017) - Foth, Christian; Ascarrunz, Eduardo; Joyce, Walter G.
Abstract : In a previous study, we estimated the cranial disparity of turtles (Testudinata) through time using geometric morphometric data from both terminal taxa and hypothetical ancestors to compensate for temporal gaps in the fossil record. While this method yielded reasonable results for the Mesozoic and the early Cenozoic, we found a large drop in cranial disparity for the Miocene, for which we found no correlation with known environmental changes or extinction events. Instead, we speculated that the Miocene dip was a result of poor sampling of fossils or ancestors in this time bin. To countervail this problem, we here updated our original dataset and interpolated changes of shape along the branch lengths and compared them with the previous data. We furthermore explored the impact of topological and temporal uncertainty, demonstrating that the Miocene dip, indeed, is a sampling artefact. All remaining conclusions of the previous study could be more or less supported, nevertheless, including an apparent correlation with global biogeographic events, a minor correlation between cranial disparity and global temperature, and resilience across the K/T extinction event.